Model Pemetaan Konflik dalam Perencanaan Pembangunan Berkelanjutan - Nur, Hamdi (TINGKAP, 2010)
ABSTRACT The goals for planning in sustainable development are promoting economic growth, advocating social justice and protecting green areas. It is not a coherent concept because there are conflict interests among these goals. Sustainable development as a normative concept is vulnerable to question whether it is a useful model to guide planning practice. To achieve sustainable planning goals, these conflicting interests must be reconciled. The conflicts between divergent interests lead to three associated conflicts, that is property conflict, resource conflict, and development conflict. Triangular modelÂ  of conflicting goals for planning and the three associated conflicts can be used as a model to guide planning practice on sustainable issues. Kata Kunci: sustainable development, conflict interest, triangular model